Colistin in Pig Production: Chemistry, Mechanism of Antibacterial Action, Microbial Resistance Emergence, and One Health Perspectives - Rhouma, Mohamed; Beaudry, Francis; Thériault, William; Letellier, Ann (Frontiers in Microbiology, 2016)
Colistin (Polymyxin E) is one of the few cationic antimicrobial peptides commercialized in both human and veterinary medicine. For several years now, colistin has been considered the last line of defense against infections caused by multidrug-resistant (MDR) Gram-negative such as Acinetobacter baumannii, Pseudomonas aeruginosa, and Klebsiella pneumoniae. Colistin has been extensively used orally since the 1960s in food animals and particularly in swine for the control of Enterobacteriaceae infections. However, with the recent discovery of plasmid-mediated colistin resistance encoded by the mcr-1 gene and the higher prevalence of samples harboring this gene in animal isolates compared to other origins, livestock has been singled out as the principal reservoir for colistin resistance amplification and spread. Co-localization of the mcr-1 gene and Extended-Spectrum- β-lactamase (ESBL) genes on a unique plasmid has been also identified in many isolates from animal origin. The use of colistin in pigs as a growth promoter and for prophylaxis purposes should be banned, and the implantation of sustainable measures in pig farms for microbial infection prevention should be actively encouraged and financed. The scientific research should be encouraged in swine medicine to generate data helping to reduce the exacerbation of colistin resistance in pigs and in manure. The establishment of guidelines ensuring a judicious therapeutic use of colistin in pigs, in countries where this drug is approved, is of crucial importance. The implementation of a microbiological withdrawal period that could reduce the potential contamination of consumers with colistin resistant bacteria of porcine origin should be encouraged. Moreover, the management of colistin resistance at the human-pig-environment interface requires the urgent use of the One Health approach for effective control and prevention. This approach needs the collaborative effort of multiple disciplines and close cooperation between physicians, veterinarians, and other scientific health and environmental professionals. This review is an update on the chemistry of colistin, its applications and antibacterial mechanism of action, and on Enterobacteriaceae resistance to colistin in pigs. We also detail and discuss the One Health approach and propose guidelines for colistin resistance management.